Transfers, Netzwerke und produktive Missverständnisse:: Plastic People, Velvet Underground und das Verhältnis zwischen westlicher und östlicher Dissidenz 1965–1978 - Esch, Michael (Comparativ, 2014)
Transfers, Networks, and Productive Misunderstandings: Plastic People, Velvet Underground, and the Relations Between Western and Eastern Dissidence 1965–1978 The history of pop and rock music and related youth subcultures in the ČSSR and especially the Prague underground have traditionally been depicted as a story of a somewhat repressed transfer, where youngsters inspired by western pop cultural promises of freedom tried to rebel against the sinister authorities of their homeland. Following, in a transnational perspective, the history of one particularly important underground band, the Plastic People of the Universe, the article nevertheless argues that the Prague underground defined itself as part of a cultural revolutionary movement rejecting the consumerist aspects of both eastern and western societies. The study also shows that an assessment of the Prague underground as merely receptive, imitative of western role (and musical) models is erroneous. The relationship between the new popular and underground music and their respective subcultures in the West and in Prague is more adequately described in terms of appropriation and invention triggered by what young rebels encountered through official and unofficial media. Czech actors used elements of western underground culture for purposes of self-expression because they perceived these as reactions to phenomena and problems comparable to what they experienced in their own lives. Nonetheless, when two Plastic People musicians were convicted in 1977, the political and religious opposition organised around Charta 77 regarded and represented them as anticommunist dissidents. This alliance between organised dissidence and the hippie underground did not last very long, yet it impacted both on the band’s (musical) practices and their image within the western musical underground as critiques of the socialist system.